The Effect Of Compost Of Empty Palm Oil Bunches To The Growth And Yield Of Marigold On Alluvial Soil - ., rafika; Dupa Bandem, Putu; Zulfita, Dwi (Jurnal Sains Pertanian Equator, 2019)
Marigolds are ornamental plants with high ekonomic and a high prospective value cultivated. Application of compost of empty palm oil bunches have an important role in improving the physical properties of the alluvial soil. This study aims to find the best compost dose of compost of empty palm oil bunches on the growth and yield of marigold plants on alluvial soil. This research was carried out on Faculty of Agriculture of Tanjungpura University experimental garden in Pontianak which took place from March 21st to Mei 22th 2019. The method used was Completely Randomized Design (CRD) consisted of 5 treatment levels, 5 replications, and 4 sample plants. Application of the treatment were t1 = 400 g/polybag, t2 = 800 g/polybag, t3 = 1200 g/polybag, t4 = 1600 g/polybag, and t5 = 2000 g/polybag. The observed varibles were plant height, leaf number, flowering age, root volume, dry weight of plants, number of flowers. The results showed that the dose of compost of empty palm oil bunches had not yet been found to provide differences or variability to growth and yield of marigold on alluvial soils.